Considerations on the application of miniaturized sample preparation approaches for the analysis of organic compounds in environmental matrices - Pena-Pereira, Francisco (2019)
The miniaturization and improvement of sample preparation is a challenge that has been fulfilled up to a point in many fields of analytical chemistry. Particularly, the hyphenation of microextraction with advanced analytical techniques has allowed the monitoring of target analytes in a vast variety of environmental samples. Several benefits can be obtained when miniaturized techniques such as solid-phase microextraction (SPME) or liquid-phase microextraction (LPME) are applied, specifically, their easiness, rapidity and capability to separate and pre-concentrate target analytes with a negligible consumption of organic solvents. In spite of the great acceptance that these green sample preparation techniques have in environmental research, their full implementation has not been achieved or even attempted in some relevant environmental matrices. In this work, a critical review of the applications of LPME and SPME techniques to isolate and pre-concentrate traces of organic pollutants is provided. In addition, the influence of the environmental matrix on the effectiveness of LPME and SPME for isolating the target organic pollutants is addressed. Finally, unsolved issues that may hinder the application of these techniques for the extraction of dissolved organic matter from environmental samples and some suggestions for developing novel and less selective enrichment and isolation procedures for natural organic matter on the basis of SPME and LPME are included.